ChemInform Abstract: Helicenes with Embedded Phosphole Units in Enantioselective Gold Catalysis. Issue 29 (22nd July 2014) - Yavari, Keihann; Aillard, Paul; Zhang, Yang; Nuter, Frederick; Retailleau, Pascal; Voituriez, Arnaud; Marinetti, Angela
Abstract The use of phosphahelicenes as chiral ligands in transition‐metal catalysis is described for the first time.